Tandem mass tag-based quantitative proteomic analysis of effects of multiple sevoflurane exposures on the cerebral cortex of neonatal and adult mice - Feng, Jingyu; Lin, Hua; Zhao, Yue; Yang, Yongyan; Zhuang, Xiaoli; Yu, Yang; Yu, Yonghao (Frontiers in Neurology, 2022)
Introduction Sevoflurane is the most commonly used general anesthetic in pediatric surgery, but it has the potential to be neurotoxic. Previous research found that long-term or multiple sevoflurane exposures could cause cognitive deficits in newborn mice but not adult mice, whereas short-term or single inhalations had little effect on cognitive function at both ages. The mechanisms behind these effects, however, are unclear. Methods In the current study, 6- and 60-day-old C57bl mice in the sevoflurane groups were given 3% sevoflurane plus 60% oxygen for three consecutive days, each lasting 2 hours, while those in the control group only got 60% oxygen. The cortex tissues were harvested on the 8th or 62nd day. The tandem mass tags (TMT)pro-based quantitative proteomics combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis, Golgi staining, and western blotting analysis were applied to analyze the influences of multiple sevoflurane anesthesia on the cerebral cortex in mice with various ages. The Morris water maze (MWM) test was performed from postnatal day (P)30 to P36 or P84 to P90 after control or multiple sevoflurane treatment. Sevoflurane anesthesia affected spatial learning and memory and diminished dendritic spines primarily in newborn mice, whereas mature animals exhibited no significant alterations. Results A total of 6247 proteins were measured using the combined quantitative proteomics methods of TMTpro-labeled and LC-MS/MS, 443 of which were associated to the age-dependent neurotoxic mechanism of repeated sevoflurane anesthesia. Furthermore, western blotting research revealed that sevoflurane-induced brain damage in newborn mice may be mediated by increasing the levels of protein expression of CHGB, PTEN, MAP2c, or decreasing the level of SOD2 protein expression. Conclusion Our findings would help to further the mechanistic study of age-dependent anesthetic neurotoxicity and contribute to seek for effective protection in the developing brain under general anesthesia.